Standardized Preparation for Fecal Microbiota Transplantation in Pigs - Hu, Jun; Chen, Lingli; Tang, Yimei; Xie, Chunlin; Xu, Baoyang; Shi, Min; Zheng, Wenyong; Zhou, Shuyi; Wang, Xinkai; Liu, Liu; Yan, Yiqin; Yang, Tao; et al. (Frontiers in Microbiology, 2018)
The intestine of pigs harbors a mass of microorganisms which are essential for intestinal homeostasis and host health. Intestinal microbial disorders induce enteric inflammation and metabolic dysfunction, thereby causing adverse effects on the growth and health of pigs. In the human medicine, fecal microbiota transplantation (FMT), which engrafts the fecal microbiota from a healthy donor into a patient recipient, has shown efficacy in intestinal microbiota restoration. In addition, it has been used widely in therapy for human gastrointestinal diseases, including Clostridium difficile infection, inflammatory bowel diseases, and irritable bowel syndrome. Given that pigs share many similarities with humans, in terms of anatomy, nutritional physiology, and intestinal microbial compositions, FMT may also be used to restore the normal intestinal microbiota of pigs. However, feasible procedures for performing FMT in pigs remains unclear. Here, we summarize a standardized preparation for FMT in pigs by combining the standard methodology for human FMT with pig production. The key issues include the donor selection, fecal material preparation, fecal material transfer, stool bank establishment, and the safety for porcine FMT. Optimal donors should be selected to ensure the efficacy of porcine FMT and reduce the risks of transmitting infectious diseases to recipients during FMT. Preparing for fresh fecal material is highly recommended. Alternatively, frozen fecal suspension can also be prepared as an optimal choice because it is convenient and has similar efficacy. Oral administration of fecal suspension could be an optimal method for porcine fecal material transfer. Furthermore, the dilution ratio of fecal materials and the frequency of fecal material transfer could be adjusted according to practical situations in the pig industry. To meet the potential large-scale requirement in the pig industry, it is important to establish a stool bank to make porcine FMT readily available. Future studies should also focus on providing more robust safety data on FMT to improve the safety and tolerability of the recipient pigs. This standardized preparation for porcine FMT can facilitate the development of microbial targeted therapies and improve the intestinal health of pigs.